Developing capacity to accelerate scaling of climate-smart agriculture in West and Central Africa: Lessons learnt from the regional capacity building initiative - Kpadonou, Gbedehoue Esaie; Ganyo, Kyky Désiré; Segnon, Alcade C.; Zakari, Sissou; Lamien, Niéyidouba; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Effective mainstreaming of climate-smart agriculture in agricultural policy and programs requires sustained capacity development. Thus, building and expanding technical capacity of agricultural development actors has the potential of enabling scaling of CSA technologies and innovations. In collaboration with the West and Central African Council for Agricultural Research and Development (CORAF) and in synergy with the Food System Resilience Program (FSRP), AICCRA has organized a regional capacity building workshop on climate-smart agriculture for National Agricultural Research Systems (NARSs) in West and Central Africa regions. This report documents the achievements and lessons learnt from the regional capacity building initiative. Specifically, the training program consisted of four interlinked modules: (i) the climate system, its components, and how its variations affect the earth system, (ii) how to analyze an agricultural system in the face of climate change, (iii) the concept of climate smart agriculture and how to evaluate agricultural practices, technologies and innovations and (iv) how to design, write and implement CSA projects and how to integrate CSA in ongoing projects. The capacity building focused on CSA concepts, and approaches and tools for scaling. About 31% of the 52 participants (30 from West Africa and 22 from Central Africa) were women. The training workshops enabled participants to learn tools and approach to objectively evaluate the climate-smartness of agricultural practices and technologies and how to mainstream CSA in ongoing projects and design a new CSA projects. Participants expressed their intention to apply the new knowledge for integrating CSA in their ongoing projects, developing new CSA projects. To contribute to the acceleration of CSA in West and Central African regions, most of the participants have decided to initiate such a training at country level as next-step activity.